DOXORUBICIN INDUCED COGNITION IMPAIRMENT IN RAT MODEL - Wagawade, Jyoti D; Roy, Subarna; Hullatti, Kirankumar; Khode, Nisha R; Pednekar, Harsha; Hegde, Harsha V; Kholkute, Sanjiva D (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Doxorubicin (DOX) is a chemotherapeutic agent commonly used to treat a variety of cancers despite having well documented adverse side effects in organs like heart, liver, and kidney. The damage caused to brain, if any, and to what extent is, however, still not clear and the present study was undertaken to estimate the possible role of DOX inducing cognitive impairment in Wistar rats. Methods: The study carried out in two groups of Wistar rats (n=6) with one group receiving DOX, and the other only normal saline used as control. During and after the experimentation period cognitive level of each rat was measured using Barnes maze (BM) till 8 weeks. At the end of the observation period (after 8th week), a series of biochemical and histopathological studies were carried out after sacrificing the animals. Results: Errors to reach target and time taken to reach the target was found in BM experiment, elevated levels of antioxidants and hemoglobin was found reduced significantly in the DOX treated group when compared to the controls while histopathology of brain cells of DOX treated group also showed reduction in hippocampal cellularity and cell death in hippocampal area suggesting evidence of oxidative damage caused by DOX treatment. Conclusion: Parameters in this study which not only conclusively show the damage caused to brain by DOX, but also estimates the changes caused to each indicator by this drug. Keywords: Chemotherapy, Brain, Hippocampus, Oxidative stress.